Strategi Komunikasi Pemasaran Dinas Pariwisata Kabupaten Dharmasraya Dalam Mempromosikan Festival Pamalayu - Sasmita, Wilda; Edlina, Ria (CV. ITTC INDONESIA, 2024)
The Dharmasraya Regency Tourism Office faces various reasons that lead to failure in promoting the Pamalayu Festival. Seeing the challenges faced by the Tourism Office in promoting this festival, researchers are interested in digging deeper into the communication strategies used. The purpose of this study is to find out how the Communication Strategy of the Dharmasraya Regency Tourism Office is in Promoting the Pamalayu Festival. The research method used in this study used a qualitative descriptive approach with qualitative research. Data were collected using in-depth interviews and documentation methods for informants. Data analysis used data collection, data reduction, data presentation, and conclusion. The theory used in this study namely Laswel's communication theory. Lasswell states that the best way to explain the communication process is to answer the question: who says what in which channel to whom with what effect (who says what through what channel to whom with what effect). The answer to Lasswell's paradigmatic question is the elements of the communication process, namely the communicator, message, media/channel, receiver, and effect. The results of this study indicate that the strategy used by the Dharmasraya district tourism office in promoting the Pamalayu festival is with multimedia campaigns, campaigns with print media, cross-regional collaboration, and involving local communities. While the inhibiting factors for the marketing communication strategy of the Pamalayu Festival are limited access to technology, lack of human resources, and ignorance or ignorance.